+0  
 
0
82
1
avatar+3027 

Help 2,3

NotSoSmart  May 16, 2018
 #1
avatar+88898 
+1

2.  We  can represent this as

 

3^(1/3)  / 4^(1/3)      multiply top/bottom  by   4^(2/3)

 

[3^(1/3) * 4^(2/3)  / [ 4^(1/3) * 4^(2/3)  ]  =

 

[ 3^1  * 4^2 ] ^(1/3)  /  4   =

 

[ 48]^(1/3)  / 4  =

 

[ 8 * 6 ]^(1/3)  / 4  =

 

2 * [ 6] ^(1/3)  / 4  =

 

6^(1/3)  / 2   ⇒  second answer

 

 

 

 

3.   27^(1/3)   = cube root of 27   = 3

 

 

 

cool cool cool

CPhill  May 16, 2018

33 Online Users

avatar
avatar
avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.